(untitled) (Tanzania Medical Journal, 2025)
Background Critical illness during pregnancy and puerperium may result from -associated complications, non-obstetric medical illness, or preexisting conditions. The best outcome for both maternal and neonates depends on the multidisciplinary approach, from the involvement of obstetricians, neonatologists, physicians or surgeons and critical care physicians. Muhimbili national hospital’s obstetric critical care unit is still in the early stage, therefore there is a need to study the clinical profiles and treatment outcomes of critically ill obstetric patients for further improvement of maternal health care. Methods A cross-sectional facility-based study was conducted using 257 case files of women who were admitted to the obstetric intensive care unit during pregnancy or puerperium from November 2017 to December 2018 at Muhimbili National Hospital. The socio-demographic characteristics, indications for admission, interventions given, and maternal and fetal outcomes were retrieved from the case files and charts using a checklist. Statistical software version 23 was used and the descriptive statistics were presented in frequency and summarized in tables. Results Over a fourteen-month study period, 10,112 women were delivered at Muhimbili National Hospital, and 0.25% were admitted to the Obstetric intensive care unit with a mean age of 28±6.6 SD. Most patients were multiparous and admitted during the postpartum period. Obstetric hemorrhage (33.1%) and pregnancy-related hypertension with its complications (45.5%) were the leading causes of admissions. The most common interventions done were blood transfusion (53.3%), anticonvulsants (31.1%) and mechanical ventilation (28.8%). Overall, the fatality rate among women admitted to Intensive care unit was 20%. Conclusion Critically ill obstetric patients were relatively young in our study population, mostly admitted due to obstetric hemorrhage and pregnancy-related hypertension. Morbidity and Mortality associated with these conditions are preventable by emphasizing on early detection and involvement of a multidisciplinary team with increased access to a dedicated intensive care unit and high dependency unit.